Simultaneous blue and green lasing of GaN-based vertical-cavity surface-emitting lasers. (15th September 2017) - Xu, R B; Mei, Y; Zhang, B P; Ying, L Y; Zheng, Z W; Hofmann, W; Liu, J P; Yang, H; Li, M; Zhang, J
Abstract: Using a quantum dot in quantum well (QD-in-QW) active region, current injected GaN-based vertical-cavity surface-emitting lasers (VCSELs) lasing simultaneously in blue and green were achieved at room temperature (RT). Lasing was first achieved at 545 nm with a threshold current of ∼2 μ A, and with a further increase of current, another lasing peak at 430 nm came out with a threshold current of ∼5 mA. The energy difference between the two lasing peaks originating from QDs and QWs is 609 meV. According to the spontaneous emission spectra measured under different injected currents, a model of energy states in QD-in-QW is proposed to describe the distribution of carriers in this structure. Using this model, the evolution of emission intensity, shift of peak energy, variation of linewidth and the lasing characteristics can be well explained.